Sistem Informasi Realisasi Anggaran Pada Dinas Pertanian Provinsi Aceh Berbasis Web - Baizah, Zaharatul; Akbar, Rizaldi; Ismail (Jurnal Ilmu Komputer dan Teknologi Informasi, 2024)
The Budget Realization Information System at the Aceh Provincial Agriculture Service is a web-based platform that changes the way budget funds are managed and monitored in the agricultural sector. With a professional approach that focuses on system requirements analysis, careful design, measurable implementation, and comprehensive evaluation, providing effective and efficient solutions in managing budgets with a high level of transparency and accountability. real-time monitoring and reporting of budget expenditures via a web platform that is easily accessible to various related parties. The existence of the Budget Realization Information System is expected to be able to overcome challenges in managing public funds, such as potential deviations or discrepancies between budget allocations and their actual implementation. With the Budget Realization Information System, the budget management process becomes more structured and well monitored, providing timely information to stakeholders. The Realization Information System is an important breakthrough in increasing efficiency and accountability in the use of public funds in the agricultural sector of Aceh Province. It is hoped that the Budget Realization Information System can create a more transparent and accountable environment, thereby supporting sustainable growth and development in the region